Effects of wheel and hand-rim size on submaximal propulsion in wheelchair athletes - Mason, B. S.; Van Der Woude, L. H.; Tolfrey, K.; Lenton, J. P.; Goosey-Tolfrey, V. L. (Medicine & Science in Sports & Exercise, 2012)
Purpose: This study aimed to investigate the effects of fixed gear ratio wheel sizes on the physiological and biomechanical responses to submaximal wheelchair propulsion.